LIQUID CHROMATOGRAPHY-TANDEM–MASS SPECTROMETRY BIOANALYTICAL TECHNIQUE FOR ESTIMATING FAVIPIRAVIR IN PHARMACEUTICAL DOSE FORMS, BOTH IN BULK AND IN COMBINATION - KIRAN KUMAR GANTA,; RAJA SUNDARARAJAN, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The aim is to develop a simple, straightforward, quick, and accurate LCMS/MS bioanalytical technique for estimating favipiravir in pharmaceutical dose forms, both in bulk and in combination. Methods: Phenyl column using an isocratic separation with a 40:60 buffer and acetonitrile combination as the mobile phase and a buffer containing 1 mL of formic acid in 1 L of water. Results: An excellent linear range of 2 ng/mL to 40 ng/mL (r2=0.9997) was analyzed in the 10-min analysis. Favipiravir shows an LOD of 1 ng/ml (s/n = 4) and an LOQ of 10 ng/ml (s/n = 24). Accuracy, linearity, specificity, precision, system suitability, stability, and recoveries study results are all within the limits. Conclusion: In accordance with the U.S. Food and Drug Administration criteria, the proposed method was concluded to be suitable for regular evaluation and used for determining the amount of a specific drug component in tablet dosage form. The medicine remained stable during the stability experiments.